Towards international peace and security: learning from the Prophet of Islam (S.A.W.) - Mohd Kamal, Mohd Hisham (Serials Publications, 2007)
This article highlights the problems that are affecting international peace and security and suggests to the international community to learn from the exemplary conduct of the Prophet of Islam (S.A.W.)in taking up arms for exclusively defensive pruposes, fulfilling treaty obligations, establishing justice and having mercy for humankind.